Long-Term Stability of (Ti/Zr/Hf)CoSb1-xSnx Thermoelectric p-Type Half-Heusler Compounds Upon Thermal Cycling - Rausch, Elisabeth; Balke, Benjamin; Ouardi, Siham; Felser, Claudia (Energy Technology, 2015)
The effect of thermal cycling upon the thermoelectric performance of state-of-the-art p-type half-Heusler materials was investigated and correlated with the impact on the structural properties. We simulated a heat treatment of the material similar to actual applications in the mid-temperature range, such as occurs during the energy conversion from an automotive exhaust pipe. We compared three different compositions based on the (Ti/Zr/Hf)CoSb1-xSnx system. The best and most reliable performance was achieved using Ti0.5Hf0.5CoSb0.85Sn0.15, which reached a maximum figure of merit ZT of 1.1 at 700°C. The intrinsic phase separation and resulting microstructuring, which are responsible for the outstanding thermoelectric performance, were stable even after 500heating and cooling cycles. The standard deviation of the obtained ZT values lies within 2-3%, which is significantly smaller than the measurement errors.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Energy conversion; Half-Heusler compounds; Semiconductors; Thermal stability; Thermoelectrics